FENOMENA TIK TOK DAN PERAN GURU DALAM PENANAMAN NILAI - NILAI PENDIDIKAN ISLAM - Khosla, Nur Hawadatul; El - Yunusi, Muhammad Yusron Maulana (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The phenomenon of using tik-tok among children and teenagers can have positive and negative impacts on them, but the effects of addiction and emotional release are challenges for teachers in the process of implementing moral values in the character education of their students, both in children and teenagers. This research is a library research, or qualitative research, by collecting data from qualitative sources from various books, books, journals and other scientific works as reference sources and then analyzed critically. This research seeks to reveal the role of teachers in instilling moral values to deal with the TikTok phenomenon in the digital era. The results of this research show that the TikTok phenomenon in the digital era has had both positive and negative impacts on the world of education. The positive impacts include; creativity and self-expression, education and information, inspiration and motivation. Meanwhile, the negative impacts of using TikTok include content that is not suitable for children, opportunities for bullying and negative comments, excessive device usage time and loss of concentration and productivity, so in this case it is important to have the role of teachers in the digital era as learning facilitators, personal mentors, creativity in teaching information management, developing digital skills, monitoring and evaluation, professional development. Apart from that, the teacher's role is also important in instilling moral values and character education, including character development, changing bad habits into good ones, including the effects of addiction and emotional release.